Manajemen Strategik Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Guru - Amri, Yusril; Suwandi, Suwandi (STAI Auliaurrasyidin Tembilahan, 2023)
The concept of strategic management is the most appropriate way to apply in managing educational institutions. This study aims to describe strategic management of principal's leadership in improving teacher quality at SMPIT Ar-Ruhul Jadid Jombang. The research used a qualitative approach. Observation, interviews and documentation are ways to collect data in this study. The data analysis stage uses data reduction, data display, and inference, The results of the study found that: The strategic management of the principal's leadership is as follows; (Observation of the school environment and outside the school), (formulating and developing strategies through monthly and annual meetings), implementing strategies by means of coordination, socialization, establishing good relationships, and supervision), evaluating strategies through weekly, monthly, and annual meetings). The quality of teachers can be said to be of high quality seen from the factors of teacher sincerity, teacher discipline, and teacher performance. Furthermore, regarding the strategic management of the principal's leadership in improving the quality of teachers by teacher professional development, increasing teacher motivation, supervising, and evaluating.